Perceptions of acute hospital occupational therapy services: developing a new model of care for occupational therapy on acute medical wards. (2nd December 2019) - Kingston, Gail; Pain, Tilley; Murphy, Kym; Bennett, Michelle; Watson, Michelle
Abstract : Background/Aims: This study was conducted at a regional tertiary referral facility in Australia. It was part of a project to implement a new model of care for occupational therapy services on medical wards. Before the new model was implemented, focus groups were conducted to explore the perceived role of the occupational therapist on the acute medical ward, identify potential barriers to changing the service and garner support for the change in service. Methods: Three focus groups were held. The groups consisted of nursing, physiotherapy and speech pathology staff who worked on acute medical wards. Participants were asked for their perception of the role of occupational therapy on the acute medical ward. Audio-recordings of the groups were transcribed and analysed. Results: Qualitative content analysis highlighted the following themes: assessment of patient function; 'safe discharge'; more than assessment; equipment and home modifications; collaboration and communication; delegating tasks to assistants; and specialist intervention strategies. Conclusions: Multidisciplinary team members' overriding perception is that occupational therapists in acute care settings provide assessment of patient function for the specific purpose of safe discharge. Some participants recalled that occupational therapists had a greater role in ensuring patients returned to their chosen function through rehabilitation and home visits, suggesting support for a change to our proposed post-acute model of care. Concerns highlighted by focus group members regarding increased workload for multidisciplinary team members and loss of communication need to be addressed to ensure the change in service is successful.